Analysis of Fraction Conceptual Understanding Towards Thematic-Realistic Learning Based on Students’ Character of Curiosity (Universitas Negeri Semarang, 2019)
Background of this study is the low level of curiosity and conceptual understanding of fourth grade students of State Elementary Schools in Kendal Regency on mathematics subjects. The objectives of this study are (1) to know the effect of the character of curiosity towards of conceptual understanding obtained by students (2) to know the ability of students to understand fraction concepts after experiencing thematic-realistic learning. The method used was mixed method with sequential explanatory model. The sample in the research were all IV grade. While, the techniques of data analysis were t-test and z score test. The results of this study indicate that (1) there is a significant effect of the character of curiosity towards ability of mathematical conceptual understanding obtained by students (2) The implementation of thematic-realistic learning is able to significantly improve students' ability of mathematical conceptual understanding than the class that use conventional learning.